Pengaruh Kepemimpinan Kepala Sekolah, Disiplin Kerja dan Motivasi Kerja Guru Terhadap Kinerja Guru Honorer di SD Se Kecamatan Mejobo Kabupaten Kudus - Moh Zubaedi; Ana Sriekaningsih; Meirani Harsasi (LP. Ma'arif Janggan Magetan, 2022)
The purpose of this research is to determine whether the principal's leadership, work discipline, and teacher's work motivation can affect the performance given to the school. The method used in this research is quantitative research by measuring variables using a Likert scale and analyzing data using SPSS 21.0 for windows. This research involved 196 honorary teachers in public elementary schools throughout Mejobo District, Kudus Regency. The results showed that the correlation/relationship (R) was 0.913. It was explained that the large percentage of influence of the independent variable on the dependent variable was by testing the coefficient of determination which was the result of strengthening R (R Square) of 0.833, which means that the principal's leadership, work discipline, and motivation teacher work has an effect of 83% on teacher performance while other variables influence the rest. Whereas based on the t-test shows that the sig (one-sided) value is <0.01 out of 0.05, so H0 is rejected, and Ha is accepted according to the decision in taking the t-test that if Ha is born, then the principal's leadership, work discipline, and work motivation partially have a positive effect on teacher performance honorary elementary school in Mejobo sub-district, Kudus district. Suggestions recommended by researchers to continue to improve the performance of honorary teachers, regulations, work systems, and rewards can be paid more attention, especially to those who have served a long time as honorary teachers, and for honorary teachers themselves to further improve the quality of performance even though the status and rewards obtained are not equal to those of teachers ASN.